2014
DOI: 10.1038/srep07502
|View full text |Cite
|
Sign up to set email alerts
|

Toughening mystery of natural rubber deciphered by double network incorporating hierarchical structures

Abstract: As an indispensible material for modern society, natural rubber possesses peerless mechanical properties such as strength and toughness over its artificial analogues, which remains a mystery. Intensive experimental and theoretical investigations have revealed the self-enhancement of natural rubber due to strain-induced crystallization. However a rigorous model on the self-enhancement, elucidating natural rubber's extraordinary mechanical properties, is obscured by deficient understanding of the local hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Other studies concerning rubber fatigue resistance have shown increased crystallization at the ruptured site [38,39]. In these works, the analyzed cracks are always macroscopic, but the microscopic ligaments shown in Figure 4f are like others that are a consequence of rubber chain alignment and crystallization [40], and were also observed at microscopic scale.…”
Section: Rubber Surface Heterogeneitymentioning
confidence: 70%
“…Other studies concerning rubber fatigue resistance have shown increased crystallization at the ruptured site [38,39]. In these works, the analyzed cracks are always macroscopic, but the microscopic ligaments shown in Figure 4f are like others that are a consequence of rubber chain alignment and crystallization [40], and were also observed at microscopic scale.…”
Section: Rubber Surface Heterogeneitymentioning
confidence: 70%
“…Even though fillers likely introduce some differences in crack propagation mechanisms, Xiang et al conclusion can still be considered. In particular, they resume an interesting parallel, initially proposed by Zhou et al [87], between the mechanisms induced by SIC and those occurring with double networks. At the front of the crack tip, soft domains which might contain cavities, micro-cracks and amorphous or less crystallized rubber parts alternate with hard domains of highly orientated and more crystallized ligaments.…”
Section: Specificity Of Polymers Which Can Crystallize With Strainmentioning
confidence: 60%
“…The apparent crystallinity ( X c ) is calculated by the following equation: Xc=AcAc+Aa Where A c and A a represent the sum of areas under the crystalline and amorphous peaks in 1D integrated curve of WAXS patterns, respectively.…”
Section: Methodsmentioning
confidence: 99%